APLIKASI KLASIFIKASI PEMILIHAN JURUSAN IPA/IPS MENGGUNAKAN METODE NAIVE BAYES CLASSIFIER - Pambudi, Risma; Handayani, Dewi (Information Technology and Telematics, 2019)
ABSTRACT Student majors are the process of making a decision in choosing a field of study expertise based on the ability of self-potential and the opportunities that exist in each student, which aims to adjust the educational program to the unity of education with the conditions and potential peculiarities of students. The impact of the enactment of the student majors is that schools, especially teachers, do not know the talents and character of students in determining study programs, so there is a concern that students will experience difficulties in participating in learning which results in low student achievement. . The purpose to be issued is to create an application that can be used to create tasks based on the results of state examinations using the Naive Bayes classifier algorithm method. Which is expected to facilitate special teachers (BK) in making appropriate majors. Can be used also as material for information, references and articles and as a benchmark in guiding students.